2021
DOI: 10.3390/ijms22179247
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin, Quercetin, and Hydroxyapatite Act Synergistically against Pseudomonas fluorescens

Abstract: Pseudomonas fluorescens is an opportunistic, psychotropic pathogen that can live in different environments, such as plant, soil, or water surfaces, and it is associated with food spoilage. Bioactive compounds can be used as antimicrobials and can be added into packaging systems. Quercetin and lactoferrin are the best candidates for the development of a complex of the two molecules absorbed on bio combability structure as hydroxyapatite. The minimum inhibiting concentration (MIC) of single components and of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The protective effect of polyphenols against Alzheimer’s disease was recently reviewed by Chiara Colizzi [ 14 ]. In addition, research has shown that phenolic compounds derived from plants and fruits have a variety of beneficial biological effects, such as antioxidant, antimicrobial, anti-inflammatory, anticancer, and hepato-protective properties [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of polyphenols against Alzheimer’s disease was recently reviewed by Chiara Colizzi [ 14 ]. In addition, research has shown that phenolic compounds derived from plants and fruits have a variety of beneficial biological effects, such as antioxidant, antimicrobial, anti-inflammatory, anticancer, and hepato-protective properties [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The negative control was prepared by mixing 1 mL of distilled water with 9 mL of alcohol solution. An amount of 1 mL of each dilutant and 0.5 mL of the bacterial cultures in an exponential growth phase (10 8 CFU/mL) were added to 8 mL of Nutrient Broth (Sigma Aldrich, Milano, Italy) with a final volume of 9.5 mL, and incubated under shaking conditions at 37 °C for 2, 6, 12, and 24 h. After each incubation, bacterial concentrations were measured via a Model 680 Microplate Reader at 600 nm (Bio-rad laboratories, Segrate, Italy) [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the impact of LF is not limited to bacteria, but can also extend to antivirals [ 74 , 75 , 76 ], antiprotozoal [ 77 ], and antifungal [ 78 ] activities. Another important element to remember is that additional LF functions can only be performed in synergy with other components [ 79 , 80 ].…”
Section: General Lactoferrin Propertiesmentioning
confidence: 99%